Trajectories of perinatal depressive symptoms in South Africa - Garman, Emily Claire (Department of Psychiatry and Mental Health, 2019)
Perinatal depression, which occurs during pregnancy and within one year postpartum, is highly prevalent in South Africa. It is associated with greater risk of birth complications, poorer health outcomes and greater risk of suicide behaviours for the mother. Perinatal depression is also associated with poorer physical, cognitive, socio-emotional and behavioural development for her child. There is preliminary evidence using growth curve mixture modelling (GCMM) that the course of perinatal depression is heterogeneous, and that each course is associated with a range of risk factors and child outcomes. Most of this evidence is generated in high-income countries (HICs), however. Little is known about the course of perinatal depression in low-income settings, where women are more likely to experience social and economic adversity, and where the patterns of risk among mothers and their children are likely to differ. The overall aim of this thesis was to identify the trajectories of perinatal depressive symptoms among low-income women in South Africa, and investigate whether these were associated with specific psychosocial and economic risk factors, child outcomes and suicidal risk over time. First, the available literature on the use of GCMM to identify trajectories of perinatal depressive symptoms is systematically reviewed. Evidence, all from HICs, suggests that there are heterogenous trajectories. The most commonly reported trajectories are (i) a ‘low-risk’ trajectory, characterised by chronically low levels of depressive symptoms throughout the perinatal period, (ii) a ‘high-risk’ trajectory, characterised by chronically severe levels of depressive symptoms, and (iii) an ‘antenatal’ trajectory, with greater levels of symptoms antenatally, which naturally abate before or just after birth. How women with different trajectories differ in terms of social, economic and health-related characteristics was inconsistent. Data from two randomised controlled trials (RCTs) were then utilised to investigate the trajectories of depressive symptoms among perinatal women living in a low-income setting in South Africa. Both RCTs were conducted in Khayelitsha, a peri-urban township settlement close to Cape Town, characterised by high levels of poverty and unemployment, and high crime rates. The RCTs were the Africa Focus on Intervention Research for Mental Health, and the Philani Intervention Programme. The former was conducted among perinatal women at risk for depression during pregnancy, while the latter was conducted among all perinatal women, regardless of the severity of their depressive symptom at recruitment. No differences were found in depressive symptoms between the control and intervention arms in either RCT, so both arms were combined, where appropriate. The trajectories of perinatal depressive symptoms, identified though growth mixture modelling or latent class growth analysis, were similar to those reported in the systematic review. A high-risk trajectory was identified in both samples; it was characterised by greater socio-economic and health-related risks, including alcohol use during pregnancy and lower levels of social support, factors which differentiated women allocated to this trajectory from women who had low symptom levels or who showed a natural remission pattern over the perinatal period. Children of mothers with chronically severe depressive symptoms reported greater emotional problems at 36 months postpartum. Children of mothers who reported more severe depressive symptoms either early or later in the postpartum period also showed poorer physical growth at 18 and 36 months. Finally, a series of generalised estimating equations indicated that change in depressive symptoms among women initially at risk for depression during pregnancy was associated with change in the severity of suicidal risk during the perinatal period, but only when depressive symptoms decreased, and that among younger women and those who showed a lower risk trajectory of depressive symptoms. Relatively similar trajectories of perinatal depressive symptoms were identified among perinatal women in Khayelitsha, compared to studies in HICs. Women presented with different trajectories of depressive symptoms over the perinatal period, each with specific sets of risk factors and distinct associations with severity of suicidal risk and child outcomes over time. Depression and suicidal risk should be assessed independently from one another throughout the perinatal period. The consistently identified high-risk trajectory highlights the need to integrate health, social and economic characteristics into the identification and prevention strategies for perinatal depression. Given the limited mental health resources available at primary care level in South Africa, this thesis contributes to developing efficient methods to identify, refer and manage women who may need more intensive mental health care.